Effect of Family Role Promotion Program on Parent’s Caring Behaviors for Weight Control in Obese School-Aged Children in Palian District, Trang Province - Pichairat, Aussaree; Chansungnoen, Jiranuwat (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The main purpose of this quasi-experimental study was to compare pre- and post-intervention score of parent’s caring behaviors for weight control in obese school-aged children in Palian district, Trang province. Sixty parents of obese elementary school-aged children were recruited and assigned into control and experimental group, thirty each. The experimental group received the 4- week family role promotion program consisting of 4 activities conducted once a week within 4 weeks while the control group received a regular program. The data were collected using child caring behaviors developed by the researchers. The internal consistency reliability of the research instrument was calculated with Cronbach,s alphas coefficient of .97. The data were analyzed using percentage, standard deviation, and dependent t-test. Results: the study shown after completion of program, the parents in experiment group had statistically significantly higher average caring behavior scores than those at pre-program at P< .001. Additionally, post intervention program, the average caring behavior scores of the experimental group also statistically significantly higher than those of the control group at P < .001.